2015
DOI: 10.1007/s10856-015-5461-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of chitosan from Ganoderma lucidum mushroom for biomedical applications

Abstract: Chitin biopolymer production and its by-product chitosan show great potential. These biomaterials have great applicability in various fields because they are non-toxic, biodegradable, biocompatible, and have antimicrobial effects. The most common source of chitin and chitosan is the crustaceous shell; however, mushrooms are an alternative source for isolating these biopolymers because their cellular wall has a high content of chitin, which may be transformed into chitosan through a deacetylation reaction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 28 publications
2
31
0
4
Order By: Relevance
“…Similarly, these two sharp peaks at 10° and 20° were recorded for the chitosans from mushroom species F. pinicola and G. lucidum [25,34]. Mesa Ospina et al [34] reported that these peaks are characteristic peaks of the pure chitosan. This indicated that the purity of L. vellereus and P. ribis chitosans are low.…”
Section: Xrdmentioning
confidence: 64%
See 3 more Smart Citations
“…Similarly, these two sharp peaks at 10° and 20° were recorded for the chitosans from mushroom species F. pinicola and G. lucidum [25,34]. Mesa Ospina et al [34] reported that these peaks are characteristic peaks of the pure chitosan. This indicated that the purity of L. vellereus and P. ribis chitosans are low.…”
Section: Xrdmentioning
confidence: 64%
“…In a study conducted on crustacean chitosan, two sharp peaks at around 10° and 20° were observed [38]. Similarly, these two sharp peaks at 10° and 20° were recorded for the chitosans from mushroom species F. pinicola and G. lucidum [25,34]. Mesa Ospina et al [34] reported that these peaks are characteristic peaks of the pure chitosan.…”
Section: Xrdmentioning
confidence: 80%
See 2 more Smart Citations
“…The most common source of chitin and chitosan is the crustaceous shell; however, mushrooms are an alternative source for isolating these biopolymers because their cellular wall has a high content of chitin, which may be transformed into chitosan through a deacetylation reaction [7].…”
Section: Introductionmentioning
confidence: 99%